A Conceptual Framework for Journalistic Identity on Social Media: How the Personal and Professional Contribute to Power and Profit. Issue 2 (7th February 2022) - Mellado, Claudia; Hermida, Alfred
Abstract: In traditional news media, professional journalists are expected to follow the norms and practices created and perpetuated in the field to maintain autonomy and authority. Social media spaces lay outside these institutional boundaries, serving as public, semi-public, and private spaces for connection, interaction, publication, and amplification, as well as the commodification of the personal for users, including news professionals. This has given rise to tensions in journalism over the boundaries between the personal and the professional, and the public and the private, vis-à-vis the erosion of separation between editorial and commercial functions in journalism. This article proposes an analytical model to theorize journalistic identities in social media and how they interact with internal and external forces in digital spaces. Specifically, we address the identity (de)construction of journalists along a spectrum from professional to personal as it intersects with elements that impact identity, from publisher to product. This study expands the scope of journalism research to analyse the blurring of editorial and commercial decisions at the individual level, accounting for a break in the established relationship between publisher and product that has formed the basis of the news business for more than a century.